Editorial Special issue: Managing logistics processes and redesigning logistics networks - Dullaert, Wout; Song, Dong-Wook (European Journal of Transport and Infrastructure Research, 2007)
Transport and logistics are essential to modern societies including Europe. Not only do they enable an unprecedented mobility to individuals, they also offer us a wide variety of products and services affecting our world view and even our portrayal of mankind. The main functions being taken and provided by transport and logistics are geographic and time utility – the former is enhanced by linking scattered locations in a harmonised manner, while the latter is enhanced by offering that what is needed, at the right time. These functions become even more evident as we are now living in an era of globalisation.